Pengaruh Mind Mapping Terhadap Kemampuan Membaca Pemahaman Peserta Didik SMPN 5 Pati - Nihayatul Karimah; Ngatmini Ngatmini; Latif Anshori Kurniawan (CV. Alim's Publishing, 2024)
This research aims to determine the effect of the mind map model on the ability to read and understand descriptive text in class VII students at SMPN 5 Pati in the 2023/2024 academic year. With a quantitative type of experiment, this research uses a pre-experimental design with the form of a one-group pretest-posttest design. The population taken was 8 classes in class VII of SMPN 5 Pati. This research took samples from class VII-E and used purposive sampling techniques. The data collected was analyzed using test and non-test techniques where non-test techniques included observation and documentation. Presentation of this research data is in quantitative descriptive form. Based on the calculation results of the hypothesis test, a value of 0.000<0.005 was obtained with a significance level (α) of 5%, so it was found that the results of Ha were accepted and H0 was rejected. These results show that the mind map model influences the ability to read and understand descriptive text in class VII students at SMPN 5 Pati in the 2023/2024 academic year. The research results show that the mind mapping model can make students more active, creative, and make it easier for students to understand the content of the reading.